Stable lithium metal anode enabled by in situ formation of a Li3N/Li–Bi alloy hybrid layer. Issue 7 (4th January 2023) - Yang, Yang; Ai, Liufeng; He, Juhong; Zhang, Chuanxiang; Chen, Duo; Shen, Laifa
Abstract : A hybrid protective layer containing a Li3 N/Li–Bi alloy on the Li surface is constructed to guide dendrite-free Li deposition by accelerating Li + transport and homogenizing Li plating/stripping behavior. Abstract : A hybrid protective layer containing a Li3 N and Li–Bi alloy is fabricated on a Li-metal anode as an artificial SEI layer to guide dendrite-free Li deposition. Noteworthily, the hybrid interface could not only facilitate homogeneous Li plating but also provide rapid Li + transportation, enabling a long-term stability of ∼2400 h at 0.5 mA cm −2 with a low steady overpotential of 10 mV.